Meningkatkan Aksesibilitas Desa melalui Pemetaan Spasial Partisipatif dan Banner Informasi: Studi Kasus Desa Tri Karya Mulya - Firmansya, Deri; Nurmayanti, Dewi; Ikhasn, Meidy; Surahman, Ariski; D, Rifki Alwi Okta; Saputra, M. Yogi; Fatin, Rifa Nabila; Yulisa, Tri; Kusumah, Widdia (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2024)
This study aims to improve accessibility and spatial orientation in the community through the creation of location maps and the installation of informational banners in Tri Karya Mulya Village, Tanjung Raya District, Mesuji Regency. Using a descriptive qualitative and participatory approach, the project was carried out in five main stages: initial observation, field mapping, community data collection, map design, and banner installation. The results show that the banners displaying location maps significantly helped residents and visitors to locate public facilities, reduce directional confusion, and increase community involvement in village governance. Communicative graphic design and community participation further enhanced the effectiveness and sustainability of the project. This initiative offers a simple yet impactful model that can be replicated in other villages with similar conditions.